Why Can’t Saint Victorinus of Poetovio Be the Author of the Homily “On the Ten Virgins”? - Nikolay A. Khandoga (Warszawskie Studia Teologiczne)
The early Christian homily «On the ten virgins» for over 100 years has been a controversial work, since no strong argument has been presented by any scholar in favor of who is its author. The first group of researchers (for example, A. Wilmart, M. Špelič, M. Veronese and P. K. Dobrotsvetov) believes that its author is St. Victorinus of Poetovio, the first Latin interpreter of Holy Scripture. The second group of researchers (for example, A. Wlosok, M. Dulaey, R. Gryson and N. A. Khandoga) ascribes it to Pseudo-Victorinus of Poetovio, an unknown Latin exegete of the Gospel of Matthew. Proceeding from this, the article makes an attempt at a theological and philological analysis of several quotes from the homily «On the ten virgins» and the original works of St. Victorinus of Poetovio — the treatise «On the creation of the world», the fragment «On the life of Christ» and the interpretation of «On Revelation» — in order to identify the author of the homily. Important points in the answer to the question in the title in the article, becomes сhristology, eschatology and symbolic arrhythmology, since there is not a single one of the original works of Victorinus of Poetovio in which they are not given appropriate attention. However, in the homily «On the ten virgins» these theological themes are not adequately addressed.